Double-screw extrusion dispersing and coloring power characterization agent as well as preparation method and application thereof
By using ultramarine blue pigments of specific particle size as characterization agents, the dispersed coloring ability of the twin screw extrusion device is evaluated, and the problem of lack of rapid characterization methods in the prior art is solved, which improves the efficiency of polyolefin coloring processing and reduces maintenance costs. .
Patent Information
- Application Number
- CN202411527704.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
AI Technical Summary
The lack of dispersed coloring capability of the screw extrusion device rapidly characterizes the dispersed coloring of the screw extrusion device in the prior art leads to low processing efficiency and high maintenance costs.
Ultramarine blue pigments of specific particle sizes were used as a double-screw extrusion dispersion coloring ability characterization agent, and the extrusion dispersion coloring ability was evaluated by testing the oxidation induction time of the initial polyolefin and the colored polyolefin.
The working state of the twin screw device is quickly identified, which significantly improves the efficiency of polyolefin coloring processing, reduces maintenance costs, and does not require cleaning of the screw device.
Smart Images

Figure BDA0005109678880000081 
Figure BDA0005109678880000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer processing technology, and in particular to a twin-screw extrusion dispersion coloring ability characterization agent, a preparation method and an application thereof. Background Art
[0002] Polyolefin is a widely used polymer material. It is a type of thermoplastic resin made by polymerizing or copolymerizing α-olefins such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and some cycloolefins. Its types include polyethylene, polypropylene, polyethylene elastomer, etc. It has the advantages of abundant raw materials, low price, easy processing and excellent comprehensive performance. Untreated polyolefin products are white, and the single color of white products cannot meet the color needs of consumers. Therefore, in order to meet market demand, polyolefins are colored by pigments in the prior art so that polyolefin products can present different colors.
[0003] In the prior art, polyolefin coloring mainly adopts the blending of pigment and polyolefin, but some pigments have poor dispersibility in polyolefin and are easy to agglomerate, resulting in color spots and discoloration problems in the processed polyolefin. Therefore, in order to solve the above problems, the pigment and polyolefin are first made into masterbatches in the prior art, and then the masterbatches are blended and extruded with polyolefin. The use of masterbatches can significantly improve the problem of poor pigment dispersibility. In addition, in actual production, the screw extrusion device will also affect the coloring of polyolefin. With the increase of the service life of the screw, the wear of the kneading block, the stress caused by the eccentricity or the stress caused by the screw, the dispersion performance of the pigment will be affected. However, there is no characterization method for the extrusion dispersion coloring ability of the screw device in the prior art. At present, the extrusion dispersion coloring ability of the screw is only judged by the actual product state after extrusion. Once it is found that the actual extruded product has poor coloring performance, it is necessary to check the product raw materials and the screw device respectively, and the screw device needs to be thoroughly cleaned when checking the screw device, which is time-consuming and labor-intensive. Therefore, a technical solution that can quickly characterize the extrusion dispersion coloring ability of the screw is of great significance to the polyolefin coloring processing efficiency. Summary of the invention
[0004] In order to overcome the problem in the prior art that there is no rapid characterization of the poly extrusion dispersion coloring ability of a screw device, the present invention provides a twin-screw extrusion dispersion coloring ability characterization agent, a preparation method and an application thereof. The characterization agent is an ultramarine blue pigment with a specific particle size. When used, the characterization agent can characterize the extrusion dispersion coloring ability of the twin-screw extruder by testing the oxidation induction time of the initial polyolefin and the colored polyolefin extruded by the twin-screw extruder. The working state of the twin-screw extruder can be quickly identified, the adverse effects of the twin-screw extruder can be eliminated before processing, and the working efficiency of the polyolefin coloring processing can be significantly improved.
[0005] The specific technical scheme of the present invention is: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0006] The invention provides a twin-screw extrusion dispersion coloring ability characterizing agent, which is ultramarine blue with a specific particle size. The characterizing agent can quickly identify the extrusion dispersion coloring ability of a twin-screw extruder. During use, the twin-screw extruder does not need to be cleaned, and the extrusion coloring dispersion ability of the twin-screw extruder can be quickly characterized. The working state of the twin-screw extruder can be quickly judged, and the adverse effects of the twin-screw extruder can be avoided in advance before processing, thereby significantly improving the polyolefin coloring processing efficiency.
[0007] The twin-screw extrusion dispersion coloring ability characterization agent provided by the present invention has the following working principle: in order to ensure the thermal oxidative aging and light aging problems existing in downstream processing applications and daily use, antioxidants, light stabilizers, etc. are generally added to polyolefins, wherein antioxidants are almost necessary auxiliary agents for commercial polyolefins, wherein antioxidants are generally compounded by a main antioxidant and an auxiliary antioxidant, wherein the main antioxidant mostly adopts a hindered phenol antioxidant, and the function of the main antioxidant is to separate hydrogen free radicals and combine with alkyl peroxides generated by thermal oxidative aging to generate alkyl hydroperoxide; the auxiliary antioxidant mainly adopts phosphorous acid or sulfur compounds, and the function of the auxiliary antioxidant is a decomposition auxiliary agent of the above-mentioned alkyl hydroperoxide; the main antioxidant and the auxiliary antioxidant complement each other, and the loss rate of the main antioxidant can be significantly reduced by the auxiliary antioxidant; ultramarine blue is made of aluminum silicate or kaolin, anhydrous sodium sulfate, anhydrous sodium carbonate and sulfur as raw materials, which are dried, calcined and ground into extremely fine powder, and then oxidized in a tempering furnace, so the ultramarine blue molecular structure contains polysulfide ions S 3- and S 2- These sulfide ions have the same effect as auxiliary antioxidants, so when ultramarine blue is extruded in a twin-screw extruder, the loss rate of the main antioxidant in the polyolefin can also be reduced; therefore, when the dispersing ability of the twin screw is insufficient, ultramarine blue exists as an attached group. On the one hand, the coloring ability is reduced, and on the other hand, the sulfide ions cannot fully participate in the auxiliary antioxidant effect due to the attachment reason, coupled with the thermal oxidation effect of the metal ions of the ultramarine blue itself; therefore, when the dispersing ability of the twin screw is poor, not only the coloring ability is reduced, but the oxidation induction time of the extruded material will be less than the oxidation induction time of the polyolefin itself; conversely, when the dispersing ability of the twin screw is better, the adhesion capacity is increased, and the sulfide ions in the ultramarine blue will significantly increase the oxidation induction time of the extruded pellets because of their participation in the auxiliary antioxidant effect, and the oxidation induction time of the extruded pellets will be greater than the oxidation induction time of the polyolefin itself. Therefore, the dispersing ability and coloring ability of the twin screw can be judged by the relationship between the oxidation induction time of the extruded polyolefin and the extruded pellets of the polyolefin and ultramarine blue blend.
[0008] A method for preparing the above-mentioned twin-screw extrusion dispersion coloring ability characterizing agent comprises the following steps: grinding and sieving a crude product of ultramarine blue to prepare the characterizing agent.
[0009] Preferably, the grinding is performed using a ball mill.
[0010] Preferably, the wet grinding is performed using a grinding-aid solvent, and the grinding-aid solvent is water.
[0011] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin in a twin-screw extruder to extrude and granulate to obtain initial polyolefin, and testing the oxidation induction time of the initial polyolefin; Step 2: placing the initial polyolefin in step 1 and the characterization agent in a twin-screw extruder for blending, extrusion and granulation to prepare a colored polyolefin, and testing the oxidation induction time of the colored polyolefin; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. Compare the coefficient obtained by the test with the dispersion coefficient of the standard polyolefin. The dispersion coefficient of the standard polyolefin is tested using a single-screw extruder.
[0012] Preferably, the polyolefin includes polyethylene, polypropylene and polyethylene elastomer.
[0013] Preferably, the amount of the characterizing agent is 0.1-0.5%.
[0014] Preferably, the oxidation induction time is tested by differential scanning calorimetry.
[0015] Preferably, the polyolefin contains an antioxidant, and the antioxidant is a hindered phenol antioxidant.
[0016] The present invention also provides an application method of the above-mentioned twin-screw extrusion dispersion coloring ability characterizing agent. First, polypropylene is extruded into a twin-screw extruder as an initial polyolefin. Then, the initial polyolefin and the characterizing agent are injected into the twin-screw extruder for blending and extrusion to form a colored polyolefin. The oxidation induction time of the initial polyolefin and the colored polyolefin are tested respectively, the oxidation induction time of the initial polyolefin is recorded as t1, and the oxidation induction time of the colored polyolefin is recorded as t2. The coefficient of the screw extrusion dispersion ability is calculated, and the coefficient is recorded as a, a=(t2-t1) / t1. The coefficient is compared with the standard single-screw polyolefin dispersion coefficient to obtain the twin-screw extrusion dispersion coloring ability.
[0017] Compared with the prior art, this application has the following technical effects: The invention provides a twin-screw extrusion dispersion coloring ability characterizing agent, a preparation method and an application thereof. The characterizing agent is an ultramarine blue pigment with a specific particle size. When used, the characterizing agent can characterize the extrusion dispersion coloring ability of a twin-screw extruder by testing the oxidation induction time of an initial polyolefin and a colored polyolefin extruded by the twin-screw extruder. The characterizing agent can quickly identify the working state of the twin-screw extruder and eliminate the adverse effects of the twin-screw extruder before processing. When the technical solution is applied, there is no need to clean the screw device, and the working efficiency of polyolefin coloring processing can be significantly improved, reducing maintenance costs. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with the embodiments.
[0019] Embodiment 1: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0020] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 40:1, a screw speed of 500r / min, and a temperature of 220°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.1%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 40:1, the screw speed is 500r / min, and the temperature is 220°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 40:1, a screw speed of 500r / min, and a temperature of 220°C.
[0021] Embodiment 2: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0022] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 35:1, a screw speed of 400r / min, and a temperature of 200°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.2%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 35:1, the screw speed is 400r / min, and the temperature is 200°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 35:1, a screw speed of 400r / min, and a temperature of 200°C.
[0023] Embodiment 3: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0024] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 30:1, a screw speed of 300r / min, and a temperature of 150°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.3%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 30:1, the screw speed is 300r / min, and the temperature is 150°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 30:1, a screw speed of 300r / min, and a temperature of 150°C.
[0025] Embodiment 4: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0026] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 33:1, a screw speed of 350r / min, and a temperature of 180°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.4%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 33:1, the screw speed is 350r / min, and the temperature is 180°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 33:1, a screw speed of 350r / min, and a temperature of 180°C.
[0027] Example 5:.
[0028] A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0029] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 38:1, a screw speed of 450r / min, and a temperature of 210°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.5%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 38:1, the screw speed is 450r / min, and the temperature is 210°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 38:1, a screw speed of 450r / min, and a temperature of 210°C.
[0030] Embodiment 6: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0031] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 36:1, a screw speed of 420r / min, and a temperature of 220°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.2%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 36:1, the screw speed is 420r / min, and the temperature is 220°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 36:1, a screw speed of 420r / min, and a temperature of 220°C.
[0032] Embodiment 7: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0033] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 32:1, a screw speed of 390r / min, and a temperature of 200°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.1%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 32:1, the screw speed is 390r / min, and the temperature is 200°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 32:1, a screw speed of 390r / min, and a temperature of 200°C.
[0034] Embodiment 8: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0035] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 39:1, a screw speed of 500r / min, and a temperature of 220°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.1%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 39:1, the screw speed is 500r / min, and the temperature is 220°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 39:1, a screw speed of 500r / min, and a temperature of 220°C.
[0036] Embodiment 9: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0037] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 31:1, a screw speed of 300r / min, and a temperature of 180°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.2%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 31:1, the screw speed is 300r / min, and the temperature is 180°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 31:1, a screw speed of 300r / min, and a temperature of 180°C.
[0038] Embodiment 10: A twin-screw extrusion dispersion coloring ability characterizing agent, the characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
[0039] An application of the above twin-screw extrusion dispersion coloring ability characterization agent comprises the following steps: Step 1: placing polyolefin (Sinopec Zhenhai Refining and Chemical R546, the original granule oxidation induction time is 38min) in a twin-screw extruder (the twin-screw extruder has a length-to-diameter ratio of 34:1, a screw speed of 420r / min, and a temperature of 200°C) for extrusion and granulation to prepare initial polyolefin, and testing the oxidation induction time of the initial polyolefin according to the method of GB / T19466.6, which is recorded as t1; Step 2: The initial polyolefin in step 1 and the characterization agent (the amount of the characterization agent is 0.3%) are placed in a twin-screw extruder (the aspect ratio of the twin-screw extruder is 34:1, the screw speed is 420r / min, and the temperature is 200°C) for blending, extrusion and granulation to prepare a colored polyolefin, and the oxidation induction time of the colored polyolefin is tested according to the method of GB / T19466.6, which is recorded as t2; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. The coefficient is a. The calculation formula of the coefficient a is: a=(t2-t1) / t1. Compare the coefficient obtained by the test with the standard polyolefin dispersion coefficient. The standard polyolefin dispersion coefficient is tested using a single-screw extruder. The single-screw extruder has a length-to-diameter ratio of 34:1, a screw speed of 420r / min, and a temperature of 200°C.
[0040] Test example 1: The color difference of the initial polyolefin and the colored polyolefin obtained in Examples 1 to 10 was tested using a colorimeter, and the color difference value ΔE was tested using a colorimeter LS171. The test results are shown in Table 1. Table 1 Test results As shown in Table 1, the extrusion dispersion coloring ability coefficient a of different twin-screw extruders is calculated in Examples 1 to 10, and the color difference value ΔE of the colored polyolefin extruded by the twin-screw extruder is verified by using a colorimeter based on the colored polyolefin extruded by the standard single-screw extruder. The relationship between the a value and the color difference ΔE is compared, and the analysis results show that the extrusion dispersion coloring ability of the single-screw extruder after extrusion is excellent, and its coefficient a is 33.3, and the color difference ΔE is 0. The smaller the color difference value ΔE of Examples 1 to 10, the closer its coefficient a is to the coefficient a of the single screw, and the larger the color difference, the farther its coefficient is from the coefficient a of the single screw. Therefore, the above results show that the extrusion dispersion coloring ability of the twin-screw extruder can be characterized by ultramarine blue as a characterizing agent. In addition, through the analysis of the dosage of ultramarine blue, it was found that when the dosage of ultramarine blue was too small, the characterization effect was poor and the difference in the obtained a value was small, so it was necessary to control the dosage of ultramarine blue to be above 0.1%. In addition, the above method does not require thorough cleaning of the device when used, and can evaluate the extrusion dispersion ability of the twin-screw before production, thereby improving production maintenance efficiency and reducing production costs.
[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A twin-screw extrusion dispersion coloring ability characterizing agent, characterized in that: The characterizing agent is ultramarine blue, the particle size of the characterizing agent is less than 5 μm, the D50 of the characterizing agent is less than 2 μm, and the residue of the characterizing agent passing through a 320-mesh sieve is less than 0.1%.
2. A method for preparing a twin-screw extrusion dispersion coloring ability characterizing agent according to claim 1, characterized in that: The following steps are involved: The crude product of ultramarine blue was ground and sieved to prepare the characterizing agent.
3. The preparation method according to claim 2, characterized in that: The grinding is carried out by dry grinding or wet grinding.
4. The preparation method according to claim 2 or 3, characterized in that: The grinding is performed using a ball mill.
5. The preparation method according to claim 3, characterized in that: The wet grinding is performed using a grinding aid solvent, and the grinding aid solvent is water.
6. An application of the twin-screw extrusion dispersion coloring ability characterizing agent according to claim 1, characterized in that: The following steps are involved: Step 1: placing polyolefin in a twin-screw extruder to extrude and granulate to obtain initial polyolefin, and testing the oxidation induction time of the initial polyolefin; Step 2: placing the initial polyolefin in step 1 and the characterization agent in a twin-screw extruder for blending, extrusion and granulation to prepare a colored polyolefin, and testing the oxidation induction time of the colored polyolefin; Step 3: Calculate the coefficient of the twin-screw extrusion dispersion coloring ability. The coefficient is the ratio of the difference between the oxidation induction time of the colored polyolefin and the oxidation induction time of the initial polyolefin to the oxidation induction time of the initial polyolefin. Compare the coefficient obtained by the test with the dispersion coefficient of the standard polyolefin. The dispersion coefficient of the standard polyolefin is tested using a single-screw extruder.
7. The use according to claim 6, characterized in that: The polyolefins include polyethylene, polypropylene and polyethylene elastomers.
8. The use according to claim 6, characterized in that: The dosage of the characterizing agent is 0.1-0.5%.
9. The use according to claim 6, characterized in that: The oxidation induction time was measured by differential scanning calorimetry.
10. The use according to claim 6, characterized in that: The polyolefin contains an antioxidant, and the antioxidant is a hindered phenol antioxidant.